The Transformation of Accounting Practices in the Age of E?Commerce - Mittal, Verma Manish (Journal of Global Economy, Business and Finance, 2026)
The rapid expansion of e-commerce has brought about a great deal of change in the accounting sector, posing both new opportunities and difficulties for accountants. This study looks at how cloud-based accounting, AI-driven analytics, and automated financial systems are transforming how businesses manage and keep an eye on their finances in the digital age. Due to the large number of smaller, more frequent transactions in e-commerce, effective solutions that minimize human error and allow for real-time financial tracking are now required. Businesses may now access the most recent financial data thanks to cloud-based solutions, and AI- powered technologies improve forecasting, data analysis, and strategic decision-making.